Bibliomatric Analyze: Development of Research Publication on "General Elections In Indonesia" - Ami Afriyani; Idah Wahidah; Muhammad Taufiq Hatta Wibowo (Social Impact Journal, 2022)
The general election in Indonesia is an interesting topic to discuss, including the development of its publications. In the last five years, in 2018-2022 the published articles on general elections in Indonesia have increased every year in the Dimensions index. This is related to this research which will discuss bibliometric analysis. In this study using the literature review study method, in which the author collected databases from https://www.dimensions.ai/ which were then processed using the VosViewer tool. This study aims to see how far the development of research publications with the keyword "general elections in Indonesia" can then be used as reference material for the novelty process of future research. The results of the study show that significantly every year from 2018 to 2021 the development of general election publications in Indonesia is experiencing an increasing trend, only in 2022 it will slightly decrease. The results of the analysis using the VOS viewer show that there are 11 authors who publish. Based on keyword data, general elections in Indonesia have 7 different keyword clusters but are related to one another.